2013
DOI: 10.1007/s11882-013-0384-6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Tbx1 as a Candidate Gene for 22q11.2 Deletion Syndrome

Abstract: 22q11.2 deletion syndrome (22q11.2DS) is caused by a commonly occurring microdeletion on chromosome 22. Clinical findings include cardiac malformations, thymic and parathyroid hypoplasia, craniofacial dysmorphisms, and dental defects. These phenotypes are due mainly to abnormal development of the pharyngeal apparatus. Targeted deletion studies in mice and analysis of naturally occurring mutations in humans have implicated Tbx1 as a candidate gene for 22q11.2DS. Tbx1 belongs to an evolutionarily conserved T-box… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 82 publications
1
38
0
3
Order By: Relevance
“…[47][48][49] Additionally, the 22q11 deletion syndromes, including Velocardiofacial syndrome and DiGeorge syndrome, in which patients present with heart defects, hypoplastic thymus, and mild craniofacial defects, are also thought to be partially attributable to defects in NCCs. 71,72 p53 suppression by genetic ablation or pharmacological inhibition can partially rescue phenotypes of Tbx1 heterozygous mice, which develop features of DiGeorge syndrome, including cardiac outflow tract defects and thymic aplasia. 73 Furthermore, p53 has been reported to contribute to NCC defects in Treacher Collins syndrome, where p53 activation in Tcof1 C/¡ embryos triggers apoptosis of neuroepithelial cells and deficiencies in the formation of migrating cranial NCCs, culminating in craniofacial malformations.…”
Section: The Role Of P53 In Other Diseasesmentioning
confidence: 99%
“…[47][48][49] Additionally, the 22q11 deletion syndromes, including Velocardiofacial syndrome and DiGeorge syndrome, in which patients present with heart defects, hypoplastic thymus, and mild craniofacial defects, are also thought to be partially attributable to defects in NCCs. 71,72 p53 suppression by genetic ablation or pharmacological inhibition can partially rescue phenotypes of Tbx1 heterozygous mice, which develop features of DiGeorge syndrome, including cardiac outflow tract defects and thymic aplasia. 73 Furthermore, p53 has been reported to contribute to NCC defects in Treacher Collins syndrome, where p53 activation in Tcof1 C/¡ embryos triggers apoptosis of neuroepithelial cells and deficiencies in the formation of migrating cranial NCCs, culminating in craniofacial malformations.…”
Section: The Role Of P53 In Other Diseasesmentioning
confidence: 99%
“…It serves a crucial role in cardiovascular morphogenesis, particularly in elongating the cardiac tube at the anterior pole and maintaining the proliferation of mesenchymal precursor cells for the formation of a myocardialized and septated outflow tract (45). The expression of TBX1 varies spatiotemporally in the tissues that form the pharyngeal apparatus, which develops into the heart during embryogenesis (46). Genetic studies in mice have demonstrated that TBX1 expression during embryogenesis requires specific regulation and in patients with 22q11DS, it has been observed that increases or decreases in TBX1 transcript levels may result in developmental malformations (46)(47)(48)(49).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of TBX1 varies spatiotemporally in the tissues that form the pharyngeal apparatus, which develops into the heart during embryogenesis (46). Genetic studies in mice have demonstrated that TBX1 expression during embryogenesis requires specific regulation and in patients with 22q11DS, it has been observed that increases or decreases in TBX1 transcript levels may result in developmental malformations (46)(47)(48)(49). Furthermore, in vivo studies have identified that TBX1 is a candidate gene for 22q11DS (48)(49)(50).…”
Section: Introductionmentioning
confidence: 99%
“…Also, 12 additional T-Box1 (TBX1) probes are included in the P324 kit (the P250 kit has only two TBX1 probes) (supplementary on-line material, table 1). TBX1 is one of the most important candidate genes at 22q11.2 concerning physical abnormalities in 22q11DS [30, 31], but it is also associated with psychiatric features like autism spectrum disorders [32] and in mouse models with social interaction problems [33] and autism [34]. …”
Section: Introductionmentioning
confidence: 99%